2015
DOI: 10.2147/copd.s91742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic obstructive pulmonary disease in asymptomatic smokers

Abstract: BackgroundPhysicians do not routinely recommend smokers to undergo spirometry unless they are symptomatic.ObjectiveTo test the hypothesis that there are a significant number of asymptomatic smokers with chronic obstructive pulmonary disease (COPD), we estimated the prevalence of COPD in a group of asymptomatic smokers.MethodsTwo thousand nine hundred and sixty-one smokers with a cumulative consumption history of at least 10 pack-years, either smokers with symptoms or smokers without symptoms (WOS) were invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…Although current clinical practice guidelines recommend against screening for COPD in asymptomatic individuals, 23 , 42 , 43 there are several studies that have revealed a high prevalence of COPD among smokers with minimal or no symptoms. 44 In our study, the group of asymptomatic smokers with COPD represented 1.6% of the study participants and 21% of those who had COPD. These findings are in accordance with a previous study 37 showing that the prevalence of COPD in asymptomatic smokers has been 1.5% when considering the whole group of smokers and 7% when considering the group of nonsymptomatic smokers.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although current clinical practice guidelines recommend against screening for COPD in asymptomatic individuals, 23 , 42 , 43 there are several studies that have revealed a high prevalence of COPD among smokers with minimal or no symptoms. 44 In our study, the group of asymptomatic smokers with COPD represented 1.6% of the study participants and 21% of those who had COPD. These findings are in accordance with a previous study 37 showing that the prevalence of COPD in asymptomatic smokers has been 1.5% when considering the whole group of smokers and 7% when considering the group of nonsymptomatic smokers.…”
Section: Discussionmentioning
confidence: 70%
“…These findings are in accordance with a previous study 37 showing that the prevalence of COPD in asymptomatic smokers has been 1.5% when considering the whole group of smokers and 7% when considering the group of nonsymptomatic smokers. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the American College of Chest Physicians and the European Respiratory Society do not recommend screening of asymptomatic smokers by spirometry [ 25 ]. Indeed, the incidence of COPD in asymptomatic cigarette smokers is very low [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff COPD Assessment Test (CAT) score to identify this group may be derived from the value used in Global Initiative for Chronic Obstructive Lung Disease (GOLD) staging (<10; less-symptoms group, ≥10; more-symptoms group) [69]. A previous study showed that 13.7% of smoking-related COPD patients do not have symptoms, and 1.5% of asymptomatic smokers have airway obstruction [70]. These patients are likely to be underdiagnosed, exposed continuously to risk factors, especially tobacco smoking, and progress to overt COPD.…”
Section: Definitionmentioning
confidence: 99%